Learning Path: CompTIA A+ 220-901 and 220-902 Certification - Prowse, David (Pearson IT Certification, 2016)
Prerequisites Basic computer knowledge Overview More than 50 hours of video training covering all of the objectives in the CompTIA A+ 220-901 and 220-902 exams as well as real-world hardware builds, networking demos, troubleshooting scenarios, and more. Description CompTIA A+ 220-901 and 220-902 Certification Learning Path is a unique video product that provides complete coverage of all the CompTIA A+ 220-901 and 220-902 objectives so you can study for and pass the exams The training provided in this Learning Path which includes the CompTIA A+ 220-901 and CompTIA 220-902 Complete Video Courses plus CompTIA A+ Troubleshooting Techniques-provides targeted and concise hands-on training that walks you through a learning path to successfully understand and absorb all key exam concepts. The modules in this course cover every objective in the CompTIA A+ 220-901 and 220-902 exams and can be used as your sole resource for learning the material needed to study for and pass both A+ exams. You can also use this as a supplement to other A+ training. Additional troubleshooting concepts are discussed and analyzed so you can get quick, concise, hands-on, solutions for the real world. The videos in these courses map to the main objectives of the CompTIA A+ 220-901 and 220-902 certifications. The videos include the author building a computer live on camera so you can see first-hand how to accomplish key tasks. He also includes hands-on configuration labs; laptop, smartphone and device hardware labs; and live-action troubleshooting labs in addition to hands-on networking, OS and UI demos, real-world troubleshooting methods and security concepts and hands-on solutions. With over 50 hours of hands-on demonstrations, live training, animations, and video screencasting, this Learning Path provides all the coverage you need to pass the exams. This Learning Path includes: CompTIA A+ 220-901 Complete Video Course CompTIA A+ 220-901 Complete Video Course is a unique video product that provides a solid understanding of A+ skills. The modules in this course cover every objective in the CompTIA A+ 220-901 exam and can be used as your sole resource for learning the material needed to study for and pass the test. You can also use this as a supplement to other A+ training. There are a total 4 modules that map to the main objectives of the CompTIA A+ 220-901 exam. These modules contain 34 lessons with video totaling over 21 hours of hands-on demonstrations, audio instruction...